A new and efficient protocol for the synthesis of the key intermediate of Palbociclib. Issue 1 (January 2019) - Li, Shuting; Yang, Wanfeng; Ji, Min; Cai, Jin; Chen, Junqing
A new and efficient synthesis of 6-bromo-8-cyclopentyl-5-methyl-2-(methylsulfinyl)-pyrido[2, 3-d]pyrimidin-7(8H)-one, a key intermediate of Palbociclib, starting from thiouracil was described. This protocol involved methylation, nucleophilic substitution, bromination, nucleophilic substitution, Heck reaction, ring closure, oxidation, and bromination to afford a key intermediate of Palbociclib with approximately 35% overall yield. The advantages of this developed synthetic strategy included improved overall yield, inexpensive starting materials, and readily controllable and cleaner reaction conditions.